Implementasi Metode Qiro’ah bagi Siswa Kelas VIII SMP Maarif Ansoru Al Hasaniyah terhadap Keberhasilan dalam Membaca Al Qur’an - Erwanto, Nanang; Abdillah, Abid; Yahya Ashari, Mohamad (CV. Creative Tugu Pena, 2023)
The researcher conducted this study aiming to describe the implementation of the qiro'ah method for class VIII students of Maarif Ansoru Al Hasaniyah Middle School on success in reading the Qur’an. This type of research is descriptive qualitative research, data collection techniques were carried out using in-depth interviews and observations. The research instrument was class VIII students of Maarif Ansoru Al Hasaniyah Middle School. Maarif Ansoru Al Hasaniyah Middle School is one of the Islamic boarding schools based in Rukti Basuki Village, Rumbia District, Central Lampung Regency, Lampung Province. The results of this study indicate the implementation of the qiro'ah method for class VIII students of Maarif Ansoru Al Hasaniyah Middle School on success in reading the Qur’an. The level of ability to read the Qur’an for class VIII students of Maarif Ansoru Al Hasaniyah Middle School is relatively diverse. This is because these students come from different backgrounds so that their level of ability in reading the Qur'an is also different. Most of them are boarding schools and some are not. Keywords: Implementation Reading Qur'an, Qiro'ah Method, Boarding School